The Relationship Of Covid-19 And Chronic Disorders In Maxico. - Bangash, Sudhair Abbas; David Faijue, Darlington; Rafique, Tariq (Journal of Neonatal Surgery, 2025)
Background:The COVID-19 pandemic has disproportionately affected individuals with chronic degenerative diseases, contributing to increased morbidity and mortality worldwide. In Mexico, where such conditions are prevalent, understanding their association with COVID-19 outcomes is crucial. Objective:To identify the risk factors associated with morbidity and mortality due to COVID-19 among individuals of different age groups suffering from chronic degenerative diseases in Mexico during 2020. Methods:A systematic literature review was conducted to address the research question. Specific descriptors were used to search the DeCS and MeSH platforms, and strategies were developed to retrieve relevant studies from major health science databases, including Google Scholar, PubMed, and SciELO. The search spanned three months. Results:Eleven relevant publications were identified. The findings revealed that obesity was the most significant predictor of COVID-19 morbidity and mortality, followed by diabetes, hypertension, and chronic kidney failure. The population most affected included men over sixty years old, particularly from the states of Mexico, Veracruz, Oaxaca, and Guanajuato. Approximately 73% of patients exhibited mild outpatient symptoms. However, individuals with cerebrovascular disease, chronic kidney disease, bronchial asthma, and elevated triglyceride or cholesterol levels were at higher risk of death. Conclusion:Hypertension, diabetes, obesity, and cardiovascular diseases are the most prevalent chronic degenerative conditions associated with adverse COVID-19 outcomes. The presence of these comorbidities significantly increases the risk of morbidity and mortality in the Mexican population..